A multi-country outbreak of Salmonella Mbandaka linked to pre-cooked, frozen chicken meat in ready-to-eat products, Finland, 2022 to 2023 - Ruska Rimhanen-Finne (Eurosurveillance)
In May 2022, the Finnish Institute for Health and Welfare observed an increase in Salmonella Mbandaka cases. Whole genome sequencing (WGS) linked the outbreak strain to a previously reported strain in the United Kingdom. From April 2022 to January 2023, 97 cases were reported across 18 of Finland’s 21 hospital districts, with a median age of 27 years (range <1–74 years) and 61% female cases. Based on trawling interviews and national food consumption data, cases were more likely to have eaten at a restaurant or takeaway (odds ratio (OR) = 115; 95% confidence interval (CI): 52–256; p < 0.001) or consumed poultry products (OR = 28; 95% CI: 7–115; p < 0.001). A case–case study linked cases with consumption of ready-to-eat products containing chicken from a specific company (OR = 28; 95% CI: 1.9–1,361; p = 0.004). Traceback investigations identified a pre-cooked, frozen chicken meat product from a country outside the European Union as the likely source. Salmonella Mbandaka was isolated from cases and linked by WGS to this chicken meat product. Our findings highlight the potential health risk of pre-cooked chicken meat containing Salmonella and the value of case–case studies and product images to assist recall during food-borne outbreak investigations.